2008 UWEC Counseling Services Needs Assessment. - Baldwin, Andrew; Sage, Jenna; Crossfield, Paula; Aspinwall, Elizabeth R.; Merrill, Laura; Schoenhals, Jeanie (My University, 2009)
A 2008 University of Wisconsin--Eau Claire Needs Assessment was sent to a 20% random sample of UWEC students. The purpose of the current study was to replicate the 2000 UWEC Counseling Needs assessment which was used to assess the self-reported needs of UWEC students for UWEC Counseling Services.
2008 University of Wisconsin--Eau Claire Counseling Services Needs Assessment
Color poster with text, tables and graph describing research conducted by Jenna Sage et al., advised by Patrick J. Kennedy and Allen H. Kenniston.
Keywords: Counseling in higher education--Wisconsin--Eau Claire; Posters; Counseling in higher education--Evaluation; University of Wisconsin--Eau Claire. Counseling Services; Needs assessment